Produção de carvão vegetal e ativação térmica a partir de resíduos de bambu (Bambusa vulgaris) para adsorção de Cobre (II) - SILVA, Yuri Leon dos Santos (2019)
Activated charcoal (AC) is an essential product for removal of environmental contaminants, however the high costs of production limit your effective use in the treatment of effluents that harm communities, however several studies aim to find organic materials renewable sources, low cost and with less environmental impact. Soon, this work aims to produce charcoal from the stalk of bamboo (Bambusa Vulgaris), the landscaping process residue Woods Camilo Viana-UFPA, and activate it thermally at different temperatures to check the efficiency of the adsorption process. The bamboo was collected, washed and dried in an oven at 105º C for 24 hours. The coals were charred to 550° C for 3 hours and thermally activated the 800° C in times of 1, 2 and 3 hours and subsequently, by means of adsorption tests identified the best the approx. uptime For the characterization of vegetable coals and activated were rea overall analysis on SEM, XRD, SEM-EDS and FRX, where it was possible to determine that the activated charcoal to 800° C for 2 hours (CAB 2:00) performed as best adsorbent for adsorption of copper ions (II), with indexes above 95%, determined by the absorption method Atomic, where the pH of the solution has shown alkaline character 8.37. The morphology of the material (MEV) illustrated porous structure that, when analyzed by spectrum (EDS) confirmed your carbonácea feature for high carbon (C); Furthermore, the DRX and FRX confirmed the high presence of potassium (K) and chlorine (Cl) in the sample, which justifies the formation of mineralogical phases in submission to high temperatures.